(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To describe clinical features, estimate the prevalence of diabetic retinopathy (DR) and its risk factors in a population of diabetic patients attending at the Thong Nhat hospital in Hochiminh city (Vietnam). Methods: A Hospital – based cross-sectional study was conducted in 180 patients who were selected from diabetic population attending in Thong Nhat hospital from 03/2020 to 08/2020. All the diabetic patients underwent retinal examination by using slit-lamp biomicroscopy combined with a contact lens, dilated pupils test, captured color digital retinal fundus (CR-2 Digital Retinal Camera, Canon, Japan). Retinopathy was graded according to the “International clinical diabetic retinopathy and diabetic macular edema disease severity scales” 2018. Factors including: age, sex, time of diagnosis of diabetes, BMI, smoking, average blood sugar control levels (HbA1c), control blood pressure and dyslipidemia were recorded to analyze their associations with diabetic retinopathy. Result: The prevalence of diabetic retinopathy was 26.7%, including: mild non-proliferative diabetic retinopathy 9.4%; moderate NPDR 10%, severe NPDR 5%; proliferative diabetic retinopathy (PDR) 2.2%. Multiple logistic regression analysis showed that diabetic retinopathy was significantly associated with duration of diabetes (more than 10 years) (OR=2.36 [1.06-5.25]), HbA1c ≥ 7% (OR=4.06 [1.72-9,56]). No association was found between the presence of any diabetic retinopathy and age, sex, BMI, smoking, control blood pressure, dyslipidemia. Conclusions: This study shows that the prevalence of diabetic retinopathy in diabetic patients is similar to that of other hospitals in the country and other countries in the region. Duration of diabetes, HbA1c were the risk factors of diabetic retinopathy.